Wing symmetry in wild drosophilids (Insecta, Diptera) is not affected by season in the Brazilian Cerrado - Luciana Costa Nascimento; Francisco Das Chagas Roque Machado; Rosana Tidon (Heringeriana, 2021)
The development of an organism is a controlled process, which can be disrupted by genetic or environmental stress. Although fluctuating asymmetry is widely used as an indicator of developmental instability, its effectiveness has been questioned due to the contradictory results produced by this technique which, at least in part, probably reflects methodological inappropriateness. Here, we investigated if wing asymmetry of drosophilids increases when they develop during the dry season in the Brazilian savanna, considered a stressful season for these insects. Using protocols designed to avoid methodological problems, we analysed the wings of Zaprionus indianus and three species of the genus Drosophila (D. mercatorum, D. simulans, and D. sturtevanti). There was no significative difference in wing asymmetry in any of the four species between the dry and rainy seasons. The similar wing asymmetry levels between seasons may mean that during the dry season drosophilids are submitted to strong natural selection and the asymmetric individuals have less chance of surviving. Alternatively, environmental drought may not affect the wing symmetry. Although our study added more data to the relationship between asymmetry and stress, this discussion seems to be far from being solved.